A REVIEW ON THE IMPLEMENTATION OF INTERNATIONAL TRADE AGREEMENT IN INDONESIA - Adolf, Huala (Transnational Business Law Journal, 2020)
ABSTRACTThe implementation of international trade agreements in Indonesia has been facing various problems in practice. This article describes the current situation where the international trade agreements already signed by the Republic of Indonesia are still facing problems in its implementation. This article suggested that Indonesia should have a permanent national institution in the implementation of international trade agreements.Keywords: Indonesia, International Agreements, Implementation, National Institution.